Leveraging Influencer Marketing in Higher Education: Key Roles, Sectors, Platforms, and Influencer Types for Institutional Branding - Sasotya Pratama; Liza Agustina Maureen Nelloh (Startupreneur Business Digital (SABDA Journal), 2025)
The concept and strategies of Influencers marketing are often for tangible product or digital products over the years. However, the implementation of influencer marketing within service, especially the Higher Education (HE) sector remains underexplored, despite its success in other industries such as beauty, fashion, and e-commerce. This study aims to bridge the research gap by investigating the key roles, sectors, platforms, and types of influencers suitable for HE institutions. The objectives include identifying the roles of influencers in shaping perceptions and decision-making processes, determining the most effective sectors and platforms for influencer marketing in HE, and exploring the types of influencers best suited for promoting HE institutions. Findings indicate that credibility, trustworthiness, engagement, and social proof are critical influencer roles. The most relevant sectors are fashion, e-commerce, and health, while Instagram, TikTok, and YouTube emerge as the dominant platforms. Virtual influencers, micro-influencers, and niche influencers are identified as the most effective for HE campaigns. These insights provide actionable recommenda- tions for HE institutions to strategically adopt influencer marketing, enhancing engagement with prospective students and strengthening institutional branding.